Review of the Literature on the Impact of Teriparatide Use on Bone Healing - Bielecka, Larysa (Quality in Sport, 2025)
Introduction Fractures, especially hip fractures, represent a growing health issue in aging societies. Recovery of mobility after such an injury can be prolonged and not always complete, affecting patients' quality of life. Modern medicine is exploring methods to support healing, including parathyroid hormone (PTH) therapy, which stimulates bone tissue formation, opening new perspectives in fracture treatment. Aim of the study The objective of this study is to review current scientific reports and summarize the existing knowledge on the impact of teriparatide supplementation on bone healing after fractures. Materials and Methods A review of randomized clinical trials (RCTs) published between 2016 and 2024 regarding the impact of teriparatide use on bone healing. Four studies meeting specific selection criteria were identified. Results The majority of analyzed studies demonstrated that the use of teriparatide improves bone mineral density. This effect was particularly pronounced among patients with prolonged teriparatide administration. In certain studies (e.g., those by Lee SY and Huang), a faster bone healing process and improved radiographic outcomes were observed in patients receiving teriparatide. Patients undergoing teriparatide supplementation reported reduced pain perception and improved mobility compared to control groups, suggesting a positive impact of the therapy on patients' quality of life during the recovery period. Conclusions The use of teriparatide shows potential as an effective therapy to enhance recovery after bone fractures.